The Impact of Foreign Aid and Domestic Revenue on Government Expenditure in Nepal: An Error Correction Approach - Veetihotra Vasishtha; MS Toor (Journal of Nepalese Management and Research, 2024)
The Impact of Foreign Aid and Domestic Revenue on Government Expenditure in Nepal: An Error Correction Approach explore the impact of foreign aid and domestic revenue on government expenditure in Nepal using an Error Correction Model and time series data from 1975 to 2022. The study aimed to find both short- and long-term correlations between these factors. The empirical findings demonstrated that both foreign aid and domestic revenue had a statistically significant and favourable influence on government expenditure in the short and long term. More precisely, there was a direct correlation between a 1 percent increase in foreign aid and a 0.42 percent increase in government expenditure, while a 1 percent increase in domestic revenue was associated with a 0.58 percent increase. The Error Correction Model confirmed a cointegrating relationship, suggesting a stable equilibrium between the variables and indicating that deviations from the long-run equilibrium were corrected over time. The study concluded that external assistance and domestic resource mobilization were essential for financing government spending in Nepal. These findings underscored the importance of implementing effective policies to attract foreign aid and enhance domestic revenue collection to support sustainable economic growth.